Diseño de una máquina mezcladora de alimentos con diferentes frecuencias. Destinada al gremio de pequeños productores de animales en el recinto San Luis, del cantón Mocache 2015 - García Carranza, Andrés Alejandro (2016)
The research project arises from the need of small and medium producers of animals in the enclosure San Luis, Mocache Canton, the same as using balanced feed based on corn and vitamin supplements in order to obtain adequate development of the livestock sector , as increased production of animals and animal products, it includes optimization of feeding them that long ago it has been done manually and feed costs are directly affected by the human resource manager mixing process and quality control of homogeneous mixture of balanced and understanding within the enclosure where carried out the research study includes various dietary approaches for animals, so different raw material is corn, wheat and soybeans used to clearly intended to correspond to balanced diet, it is also important to mention the development of the livestock sector within the enclosure as is the production of animals and their derivatives, where your goal is mainly to supply farms producing chickens, pigs, shrimp, etc. Because the composition is balanced for the most part it is corn. It is vital for optimal utilization of the mixing process proper homogeneity of the mixture so that the nutrients are assimilated and fully exploited by livestock, thus obtaining a food of maximum performance. Made adequate study, a mixing machine food various frequencies, controlled by a speed variator for the mixing process, the same that satisfies the demand for local production, additionally construction drawings were made so that it can be built designed several times depending on the needs of the community in general.